From plan to market price: inflation drivers in New Uzbekistan - Davlatov, Elyor; Sági, Judit (Public Finance Quarterly, 2025)
This study analyzes the drivers of inﬂation in new phase of economic development after 2017 liberalization. Applying the Autoregressive Distributed Lag (ARDL) approach, the research examines the relationships among monetary, non-monetary and external factors of inﬂation between October 2017 and May 2025. The ﬁndings revealed that money and producer price index (PPI) had signiﬁcant impact on inﬂation in the long run. Short-run results showed strong inﬂation inertia and PPI had a statistical signiﬁcant eﬀect on CPI in the short run. The study also identiﬁed unidirectional causality from broad money to consumer price index (CPI) and from PPI to CPI with Toda and Yamamoto causality test. These insights are crucial for policymakers aiming to address inﬂationary pressures and promote long-term economic stability in Uzbekistan. Central Bank of Uzbekistan (CBU) should maintain monetary tightening to control monetary drivers of inﬂation during the liberalization. Limiting role of state and eliminating trade tariﬀs foster greater competition, thereby helping to control cost-push inﬂation.